2021
DOI: 10.1007/s40789-021-00410-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the dust-removal performance of a wet scrubber

Abstract: A variety of dust control methods are often applied in coal mines, among which the application of wet scrubbers has proven to be an efficient technology for the removal of dust in airstreams, rather than diluting or confining the dust. In this paper, a wet scrubber design was developed. Based on a self-designed experimental test platform, the total dust concentration, respirable dust concentration, air volume, and average pressure drops of wet scrubbers with 12, 16, 20, and 24 blades were measured under differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Thus, in the VCB underground mine, PSD analysis of very low moisture dust samples yield DD 2.5 fractions reaching up to 23% DD 500 . The efficiency of wetting DD in reducing coal mine worker exposure to dust, as well as in preventing coal dust explosions, is very well documented (Woskoboenko 1988;Küçük et al 2003;Kuai et al 2012;Yuan et al 2014;Ajrash et al 2017;Azam et al 2019;Hu et al 2021;Zhang et al 2021). Küçük et al (2003) and Yuan et al (2014) found that a decrease in the dust fraction below < 125 µm can be achieved by increasing the moisture content of deposited coal dust.…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…Thus, in the VCB underground mine, PSD analysis of very low moisture dust samples yield DD 2.5 fractions reaching up to 23% DD 500 . The efficiency of wetting DD in reducing coal mine worker exposure to dust, as well as in preventing coal dust explosions, is very well documented (Woskoboenko 1988;Küçük et al 2003;Kuai et al 2012;Yuan et al 2014;Ajrash et al 2017;Azam et al 2019;Hu et al 2021;Zhang et al 2021). Küçük et al (2003) and Yuan et al (2014) found that a decrease in the dust fraction below < 125 µm can be achieved by increasing the moisture content of deposited coal dust.…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…Kalman et al [23] determined the effect of the lifting force of the particles and the rotation speed on the removal rate during particle collection. Through an experimental study of dust removal efficiency, Hu et al [24] found that changes in the dust structure affect the suction efficiency. The particle composition was changed consequently to establish an empirical correlation for particles through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Hu et al [14] presented methods to improve dust removal performance by experimentally studying the effects of changes in dust composition on cleaning efficiency. Overall, the total dust and respirable dust removal efficiency were 96.81% and 95.59%, respectively.…”
Section: Introductionmentioning
confidence: 99%